2007
DOI: 10.1021/jo071221r
|View full text |Cite
|
Sign up to set email alerts
|

Hantzsch-Type Three-Component Approach to a New Family of Carbon-Linked Glycosyl Amino Acids. Synthesis of C-Glycosylmethyl Pyridylalanines,

Abstract: C-Glycosylmethyl pyridylalanines reported in this paper constitute a novel family of glycosyl amino acids that contain a pyridine ring linking the carbohydrate and amino acid residues. These amino acids may serve to prepare nonnatural glycopeptides displaying firmly bound carbohydrate fragments through a rigid and highly stable tether. A viable route to these new hybrid molecules has been opened via thermally induced Hantzsch-type cyclocondensation using an aldehyde-ketoester-enamino ester system. To one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…8 More recently pyridine-linked glycosyl alanines were prepared via Hantzsch three-component cyclocondensation. 9 The latter reaction was carried under MW irradiation to reduce the reaction time while the workup was simplified using polymer-supported reagents. The insertion of these amino acids in small peptides was demonstrated as well ( Figure 5).…”
Section: Heterocycle-linked C-glycosyl -Amino Acidsmentioning
confidence: 99%
“…8 More recently pyridine-linked glycosyl alanines were prepared via Hantzsch three-component cyclocondensation. 9 The latter reaction was carried under MW irradiation to reduce the reaction time while the workup was simplified using polymer-supported reagents. The insertion of these amino acids in small peptides was demonstrated as well ( Figure 5).…”
Section: Heterocycle-linked C-glycosyl -Amino Acidsmentioning
confidence: 99%
“…138 The scope of this methodology was later extended by the same authors to the synthesis of a variety of enantiopure C-glycosylmethyl pyridylalanines, starting from the corresponding chiral aldehydes. 139 A group of eight novel C-glycosylmethyl pyridine amino acids were achieved in 55-68% yields with total preservation of the stereocentre integrity and functional group protection. Furthermore, the same authors developed, in 2009, the first organocatalysed three-component Hantzsch reaction between a chiral C-glycosyl aldehyde, a b-diketone, and an enamine, to provide the corresponding enantiopure substituted 1,4-dihydropyridine C-glycoconjugate in 50% yield and excellent diastereoselectivity of 498% de, as shown in Scheme 1.90.…”
Section: Multicomponent Reactions Based On the Hantzsch Reactionmentioning
confidence: 99%
“…Because of their potential use as probes in glycobiology and leads in carbohydrate-based drug discovery, synthetic glycopeptides, in which the native O-or N-glycosidic linkages are replaced by C-or S-linkages, have attracted increasing attention by researchers in industry and academia in recent years. This modification is considered to provide substantial resistance to chemical and enzymatic deglycosylation, while retaining the original biological properties of the peptide [23]. Papinia and co-workers [24] demonstrated that the use of MWI allowed the rapid and high-yielding preparation of N-glycosylamino acids orthogonally protected for SPPS (solid-phase peptide synthesis).…”
Section: O-and N-glycosylationmentioning
confidence: 99%
“…Dondoni et al [23] further validated the exceptional efficacy of Hantzsch pyridine synthesis by assembling in a one-pot procedure, without added catalysts and under the simple application of MWI, three densely functionalized substrates, such as a carbohydrate, a pyridine, and an amino acid. They reported the synthesis of a novel family of heterocycle-linked C-glycosylamino acids in which the flat and rigid pyridine ring holds the two chiral bioactive entities (Figure 21.4).…”
Section: Synthesis Of Heterocyclesmentioning
confidence: 99%